Fundamentals of momentum, heat and mass transfer - Welty, James R. (New Delhi : Wiley, 2008)
"Fundamentals of Momentum, Heat and Mass Transfer, 6th Edition provides a unified treatment of momentum transfer (fluid mechanics), heat transfer and mass transfer. The new edition has been updated to include more modern examples, problems, and illustrations with real world applications. The treatment of the three areas of transport phenomena is done sequentially. The subjects of momentum, heat, and mass transfer are introduced, in that order, and appropriate analysis tools are developed"--
Chapter 1: Introduction to Momentum Transfer -- Chapter 2: Fluid Statics -- Chapter 3: Description of a Fluid in Motion -- Chapter 4: Conservation of Mass: Control-Volume Approach -- Chapter 5: Newton's Second Law of Motion: Control-Volume Approach -- Chapter 6: Conservation of Energy: Control-Volume Approach -- Chapter 7: Shear Stress in Laminar Flow -- Chapter 8: Analysis of a Differential Fluid Element in Laminar Flow -- Chapter 9: Differential Equations of Fluid Flow -- Chapter 10: Inviscid Fluid Flow -- Chapter 11: Dimensional Analysis and Similitude -- Chapter 12: Viscous Flow -- Chapter 13: Flow in Closed Conduits -- Chapter 14: Fluid Machinery -- Chapter 15: Fundamentals of Heat Transfer -- Chapter 16: Differential Equations of Heat Transfer -- Chapter 17: Steady-State Conduction -- Chapter 18: Unsteady-State Conduction -- Chapter 19: Convective Heat Transfer -- Chapter 20: Convective Heat-Transfer Correlations -- Chapter 21: Boiling and Condensation -- Chapter 22: Heat-Transfer Equipment -- Chapter 23: Radiation Heat Transfer -- Chapter 24: Fundmentals of Mass Transfer -- Chapter 25: Differential Equations of Mass Transfer -- Chapter 26: Steady-State Molecular Diffusion -- Chapter 27: Unsteady-State Molecular Diffusion -- Chapter 28: Convective Mass Transfer -- Chapter 29: Convective Mass Transfer Between Phases -- Chapter 30: Convective Mass-Transfer Correlations -- Chapter 31: Mass-Transfer Equipment -- A. Transformations of the Operators = and =2 to Cylindrical Coordinates -- B. Summary of Differential Vector Operations in Various Coordinate Systems -- C. Symmetry of the Stress Tensor -- D. The Viscous Contribution to the Normal Stress E. The Navier-Stokes Equations for Constant b and m in Cartesian, Cylindrical, and Spherical Coordinates -- F. Charts for Solution of Unsteady Transport Problems -- G. Properties of the Standard Atmosphere -- H. Physical Properties of Solids -- I. Physical Properties of Gases and Liquids -- J. Mass-Transfer Diffusion Coefficients in Binary Systems -- K. Lennard-Jones Constants -- L. The Error Function -- M. Standard Pipe Sizes -- N. Standard Tubing Gages.
Includes index.
engineering bookfair2015
Keywords: Fluid mechanics; Heat -- Transmission; Mass transfer; TECHNOLOGY & ENGINEERING / Chemical & Biochemical